2021
DOI: 10.1055/a-1453-0806
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Adrenocortical Carcinoma: Current Perspectives on Medical Treatment

Abstract: Adrenocortical carcinoma (ACC) is a rare and aggressive malignancy. For stage I and II tumors, surgery is a curative option, but even in these cases recurrence is frequent. Practical guidelines advocate a combination of mitotane with etoposide, doxorubicin, and cisplatin as first-line therapy for metastatic adrenocortical carcinoma. However, this scheme presents limited efficacy and high toxicity. The use of Imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…This, as well as the pembrolizumab monotherapy discussed above, might be expected to provide a durable response. However, it was shown that patients receiving concomitant mitotane had a higher rate of grade 3 or higher AEs than those receiving pembrolizumab alone, particularly elevation in liver enzymes 14 . Although our patient had no severe AEs, it is necessary to make a careful decision concerning the use of concomitant mitotane.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…This, as well as the pembrolizumab monotherapy discussed above, might be expected to provide a durable response. However, it was shown that patients receiving concomitant mitotane had a higher rate of grade 3 or higher AEs than those receiving pembrolizumab alone, particularly elevation in liver enzymes 14 . Although our patient had no severe AEs, it is necessary to make a careful decision concerning the use of concomitant mitotane.…”
Section: Discussionmentioning
confidence: 64%
“…However, it was shown that patients receiving concomitant mitotane had a higher rate of grade 3 or higher AEs than those receiving pembrolizumab alone, particularly elevation in liver enzymes. 14 Although our patient had no severe AEs, it is necessary to make a careful decision concerning the use of concomitant mitotane. Further research through clinical trials is necessary to assess the efficacy and safety of this combination therapy.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…The estimated 5-year survival rate is less than 50% [ 8 ], with median survival around 3–4 years [ 9 ]. For patients with organ-confined disease, 5-year survival is 60–80%; for patients with locally advanced ACC or metastatic ACCs, 5-year survival is 35–50% and 0–28%, respectively [ 10 , 11 ]. A recent epidemiological study of 2014 ACC cases in the USA from 1973 to 2014 revealed the disease mortality is 52%, with a median survival time of less than 2 years [ 5 ].…”
Section: Introductionmentioning
confidence: 99%